Essays on the adoption and intensification of conservation agricultural practices under risk - Canales Medina, Dominga Elizabeth (Kansas State University, 2016)
In recent years, great attention has been placed on conservation systems for agricultural production. Conservation practices offer economic and environmental benefits, yet conventional practices remain the prevailing system in some regions. As conservation efforts are launched by different local and federal agencies, understanding farmers’ motivations when adopting conservation practices is important to ensure the continuation of adoption through the development of programs that are tailored to meet farmers’ preferences and constraints. The purpose of the first essay was to identify the factors affecting farmers’ choice of tillage practice at the crop level. Farmer’s choice of No-till, Strip-till and Conventional tillage was modeled for dryland corn, wheat and soybean production in Kansas. The results show that tillage decisions are crop-specific and that factors such as risk aversion, baling and grazing of crop residue, crop acreage, and farmers’ approach to adopting new technologies are significant factors affecting farmers’ decisions. The second essay focused on the adoption of continuous no-till, conservation crop rotation, cover crops, and variable rate application of inputs and the effect that incentive payments, payment mechanism, and off-farm environmental benefits from conservation have on the decision to adopt. This essay also examined the risk associated with the variability of net returns and its effect on farmers’ willingness to adopt using a non-linear extended expected utility framework, allowing for the estimation of a utility parameter for net returns, farmer’s subjective judgment of probabilities, and farmers’ risk attitudes. Farmers were found to exhibit risk aversion, with an estimated risk premium of approximately 3% of net returns. Results also suggested a preference for federally-run programs and for programs with higher off-farm environmental benefits. The third essay examined the timing of adoption of continuous no-till, cover crops, and variable rate application of inputs. This study found that risk aversion delays the timing of adoption of cover crops and variable rate application of inputs. However, the timing of adoption of continuous no-till was not affected by risk aversion. Findings also indicated that farmers who consider themselves innovators adopt at a faster rate than their counterparts.
Keywords: Adoption; Risk; Willingness to accept; Stated choice; Carbon marketConservation practices; Economics, Agricultural (0503)